AN INVESTIGATION INTO TEACHER CHARACTERISTICS AND SCHOOL EFFECTIVENESS IN RELATION TO ACADEMIC PERFORMANCE OF CLASS VIII STUDENTS IN MANDERA WEST SUB-COUNTY, REPUBLIC OF KENYA - Hussein, Dr Adan Maalim (Journal of Education and Practice, 2021)
Purpose: The purpose of this study was to establish the relationship between teacher characteristics and school effectiveness in relation to students' academic performance in Kenya certificate of primary examination (KCPE). Methodology: The study was conducted in Mandera West Sub-County, Kenya and the target population comprised of teachers of 15 head-teachers, 65 teachers and 300 students of class VIII. The study applied a causal comparative research design. A questionnaire was used for data collection and document analysis. The data collected was analysed using Excel software program. Basic statistical techniques were used to analyse various items in the questionnaire. These include calculating the averages, frequencies and percentages. These statistical techniques were used to make comparisons in the various data collected. Three hypotheses were tested at the 0.05 level of significance using correlation, t-test, and single factor analysis of variance. Results: The results showed that there was a positive relationship between teacher characteristics and school effectiveness in relation to students' academic performance in KCPE. However, the analysis shows that there was a positive relationship teacher characteristics and student's academic performance. From the research finding there was a strong relationship between school effectiveness and academic performance of students. Unique contribution to theory, practice and policy: Conclusions on the variables analysed were finally drawn from these comparisons. The study concludes that school effectiveness and academic performance of students have strong relationship towards KCPE performance.